Organizing for degrowth. Beyond the business of business - Raith, Dirk (Ökologisches Wirtschaften - Fachzeitschrift, 2021)
Degrowth provides a broad vision for the much needed transformation of modern economy and society. Businesses have so far been largely exempt from that vision, however. While they must not be ignored, what could be the role of businesses and how would they need to change?